Ambient air pollutant concentrations and asthma-related hospital admissions during COVID-19 transport restrictions. (October 2022) - Kelly, C.; Kenny, P.; O'Dwyer, M.; Quintyne, K.I.
Abstract: Objectives: Exposure to air pollution is a known risk factor for asthma exacerbations and hospitalisations. This study aimed to identify if COVID-19 transport restrictions led to improvements in air quality in Dublin and if this had an impact on asthma-related hospital admissions. Study design: This was a population-based retrospective cohort study. Methods: Daily concentration levels of particulate matter (PM2.5 and PM10 ) and nitrogen dioxide (NO2 ) were obtained from the Environmental Protection Agency (EPA). The Hospital In-Patient Enquiry (HIPE) system provided the daily number of asthma-related hospital admissions in Dublin. The figures for 2018–2019 were compared with the period of transport restrictions (from March 2020). Results: During the period of transport restrictions, there was a significant decrease in mean daily concentrations in both PM2.5 (8.9 vs 7.8 μg/m 3, P  = 0.002) and NO2 (24.0 vs 16.7 μg/m 3, P  < 0.001). There was also a significant reduction in the mean number of daily asthma admissions (4.5 vs 2.8 admissions, P  < 0.001). Only NO2 showed a statistically significant correlation with asthma admissions (r = 0.132, P  < 0.001). Conclusion: Transport restrictions introduced to mitigate against COVID-19 led to lower pollutant levels and improved air quality. Previously described associations between pollutants and asthma would indicate that these improvements in air quality contributed to the reduction in asthma-related admissions. The complex nature of PM is the likely explanation for the lack of correlation between its concentration and asthma admissions, unlike NO2 whose primary source is vehicular emissions. Public Health needs to advocate for transport policies, which can improve air quality and hence improve human health.